Lung volume restriction in patients with chronic respiratory muscle weakness: the role of microatelectasis. Issue 7 (July 1993) - Estenne, M; Gevenois, P A; Kinnear, W; Soudon, P; Heilporn, A; De Troyer, A
Abstract : BACKGROUND--It is well established that patients with longstanding weakness of the respiratory muscles have a reduction in lung distensibility. Although this occurs in most patients without any radiographic changes suggesting parenchymal lung disease, it has been attributed to the development of microatelectasis. METHODS--A high resolution computed tomographic (CT) scanner was used in eight patients with traumatic tetraplegia and six patients with generalised neuromuscular disorders to look for areas of atelectasis. With the patient in the supine posture scans of 1 mm thickness were obtained at total lung capacity at intervals of 1 cm from the apex to the base of the lung. RESULTS--Vital capacity, total lung capacity, and inspiratory muscle strength were reduced to a mean of 59.5%, 73.9%, and 51.1% of predicted values, respectively. Static expiratory lung compliance was decreased in 12 of the 14 patients and averaged 69.1% of the predicted value. The CT scans revealed only small areas of atelectasis in one tetraplegic patient and in one patient with a generalised neuromuscular disorder; no parenchymal abnormality was seen in the other 12 patients. CONCLUSIONS--In many patients with chronic weakness of the respiratory muscles the reduced lung distensibility does not appear to be caused by microatelectasis. It might be related to alterations in elasticity of the lung tissue.